Goalkeeper Game: A New Assessment Tool for Prediction of Gait Performance Under Complex Condition in People With Parkinson's Disease - Stern, Rafael B.; d'Alencar, Matheus Silva; Uscapi, Yanina L.; Gubitoso, Marco D.; Roque, Antonio C.; Helene, André F.; Piemonte, Maria Elisa Pimentel (Frontiers in Aging Neuroscience, 2020)
Background: People with Parkinson’s disease (PD) display poorer gait performance when walking under complex conditions than under simple condi- tions. Screening tests that evaluate gait performance changes under complex walking conditions may be valuable tools for early intervention, especially if allowing for massive data collection. Objectives: To investigate the use of the Goalkeeper Game (GG) to pre- dict impairment in gait performance under complex conditions in people with Parkinson?s disease (PPD) and compare its predictive power with the one of the Montreal Cognitive Assessment (MoCA) test. Methods: 74 PPD (H&Y stages: 23 in stage 1; 31 in stage 2; 20 in stage 3), without dementia (MoCA cut-off 21), tested in ON period with dopaminer- gic medication were submitted to single individual cognitive/motor evaluation sessions. MoCA and GG were used to assess cognition, and the dynamic gait index (DGI) test was used to assess gait performance under complex condi- tion. GG test resulted in 9 measures extracted via a statistical model. The predictive power of the GG measures and the MoCA score with respect to gait performance, as assessed by DGI, were compared. Results: The predictive models based on GG and MoCA score obtained, respectively, sensitivities of 65% and 56% for DGI scores at a 50% specificity. Conclusion: GG is a novel tool for noninvasive screening that showed a superior predictive power in assessing gait performance under complex condition in people with PD than the well-established MoCa test.